Granuloma-Positive Crohn’s Disease - Hugh J Freeman (Canadian Journal of Gastroenterology)
BACKGROUND: The epithelioid granuloma is a characteristic histological feature of Crohn’s disease. In some pathological classification schemes, the criteria for a definite, probable or possible diagnosis have been listed, with the epithelioid granuloma indicating definite Crohn’s disease.